Respuesta :

2x2+2x-1=
4+2(-3)-1=
4+(-6)-1=
4+(-7)=
-3

Answer: 11

Concept:

Here, we need to understand the idea of evaluation.  

When encountering questions that gave you an expression with variables, then stated: "If x = a, y = b, z = c" (a, b, c are all constants), this means you should substitute the value given for each variable back to the expression.

Solve:

Given information

x = -3

Given expression

2x² + 2x - 1

Substitute values into the expression

=2(-3)² + 2(-3) - 1

Simplify exponents

=2(9) + 2(-3) - 1

Simplify by multiplication

=18 - 6 - 1

Simplify by subtraction

=12 - 1

=[tex]\boxed{11}[/tex]

Hope this helps!! :)

Please let me know if you have any questions